Effects of Boiling and Steaming Time on Physicochemical Properties of Unripe Banana Pulp and Flour - Sangnark, Arpathsra; Kunjaethong, Thanatcha; Siriwong, Nongnuch (Journal of Food Health and Bioenvironmental Science, 2023)
The effects of boiling and steaming times on physicochemical properties of unripe banana (Musa ABB cv. Kluai Namwa) pulp and unripe banana flour were investigated. Unripe bananas were boiled or steamed by using boiling water for 15, 30 and 45 min and compared unheated (raw) banana acted as a control. The hardness of unripe banana pulp significantly decreased with boiling and steaming times from 36.73 N to 24.29 and 22.97 N, respectively (p< 0.05). However, pulp brightness (L*) from both processes decreased with heating time (p< 0.05). Ash and soluble dietary fiber of unripe banana flour showed markedly increases with heating time. Whereas fat, protein, total dietary fiber, insoluble dietary fiber content and resistant starch content of the pulp decreased inversely with the boiling and steaming time. The boiling and steaming process caused the decreased pasting temperature (from about 87.23 to 67.70°C). While, breakdown and setback viscosity of unripe banana flour increased to 37.46 and 56.13 RVU, respectively. Total phenolic content (TPC) and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl, DPPH; and Ferric reducing antioxidant power, FRAP) of the flour increased directly with boiling and steaming time. Results indicated that the increase in antioxidant activity shown by DPPH and FRAP values of heated banana flour corresponded to an increase in phenolic compounds. Finally, boiled banana flour had higher TPC, DPPH and FRAP values than steamed banana flour. The findings can promote the application of boiled and steamed banana flour as a beneficial ingredient in the food industry.